2020
DOI: 10.1590/1809-2950/18033627012020
|View full text |Cite
|
Sign up to set email alerts
|

Função sexual e incontinência urinária por esforço em mulheres submetidas à histerectomia total com ooforectomia bilateral

Abstract: RESUMO O objetivo deste artigo é avaliar o índice de função sexual de mulheres submetidas à histerectomia total com ooforectomia bilateral (HT-OB), a prevalência de incontinência urinária por esforço (IUE) e sua associação com a realização desse procedimento cirúrgico em um hospital de referência em Belém (PA). Foram incluídas 162 mulheres, com vida sexual ativa, alocadas em dois grupos: aquelas que realizaram HT-OB em período superior a 12 meses (n=68), e aquelas que não realizaram (n=94). Utilizou-se o quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Five studies reported, in addition to data related to voiding dysfunction, female sexual dysfunction. 9 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 Only five studies used validated questionnaires in their data collections, the rest used standardized instruments in their respective collection fields ( Charts 1 and 2 ). The studies had a variation in patient follow-up from 3 months to 9 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies reported, in addition to data related to voiding dysfunction, female sexual dysfunction. 9 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 Only five studies used validated questionnaires in their data collections, the rest used standardized instruments in their respective collection fields ( Charts 1 and 2 ). The studies had a variation in patient follow-up from 3 months to 9 years.…”
Section: Resultsmentioning
confidence: 99%
“…The need to perform this surgery, in many cases, causes conflicting, traumatic, insecure emotions, and anxiety, generating important changes in sexual patterns and desire. 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sabe-se que os critérios para indicação de histerectomia em pacientes na menopausa incluem doenças uterinas graves não responsivas a tratamentos conservadores, sintomas uterinos persistentes e debilitantes, idade da paciente, saúde geral, desejo reprodutivo, condições associadas à histerectomia e uma avaliação completa com o médico especialista. A decisão deve ser individualizada e baseada nas necessidades e circunstâncias de cada paciente (Cruz et al, 2020).…”
Section: Introductionunclassified